Building Emotional Regulation: The Key to Academic Success and Student Resilience - Cici Nur Azizah; Ellen Prima (Konsultan Jurnal Ilmiah Indonesia, 2026)
This research aims to comprehensively examine the significance of emotional regulation in stimulating academic success and forming strong resilience in students. The dynamics of modern education expose students to high cognitive loads and complex psychosocial pressures, both in the internal school and external family environments. Using the library research method (library study), this research collects, reduces, displays and analyzes data from various relevant scientific literature, textbooks and accredited journals. The results of in-depth studies show that there is a close biological and psychological correlation between emotional stability and cognitive performance. Neuroscientifically, the amygdala hijack phenomenon has been proven to be able to paralyze the function of the prefrontal cortex as the control center for logical thinking and executive memory, thereby hampering the process of absorbing teaching material. Other findings indicate that resilience functions as a crucial mediator that transforms the distress of academic failure into motivation for adaptive improvement. To optimize these two aspects, the role of educators in creating a psychologically safe classroom climate through the implementation of a humanist-dialogical teaching style is an absolute prerequisite. The recommendations of this research point to the importance of integrating socio-emotional curriculum in college and high school settings.